A Review of Generators and Power Converters for Multi-Mw Wind Energy Conversion Systems - Espina-Gonzalez, E; Diaz-Diaz, M; Rajendran, S (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The rated power of wind turbines has consistently enlarged as large installations can reduce energy production costs. Multi-megawatt wind turbines are frequently used in offshore and onshore facilities, and today is possible to find wind turbines rated over 15 MW. New developments in generators and power converters for multi-MW wind turbines are needed, as the trend toward upscaling the dimensions of wind turbines is expected to continue. Therefore, this paper provides a detailed review of commercially available and recently proposed multi-MW wind turbine generators and power converters. Furthermore, comparative analyses indicate the advantages and disadvantages of commercially available and promising technologies for generators and power converters at the multi-MW target. © 2022 by the authors.